Preservation of phytase enzyme produced by anaerobic rumen bacteria, Mitsuokella jalaludinii (Journal of Biochemistry, Microbiology and Biotechnology, 2017)
Poultry feed consists of feed ingredients like soybean meal and corn, which contain high levels of phytate that is poorly utilised especially by the monogastric animals that lack of phytase. Hence, phytase has been extensively applied as a feed supplement in poultry production due to the efficiency of this enzyme in improving phosphorous (P) availability, thus reducing P excretion to the environment as well as reducing the feed cost by reducing inorganic P supplementation. Mitsuokella jalaludinii, an obligate anaerobe, Gram-negative rumen bacterium, produces high phytase activity. Birds supplemented with bacterial preparation of M. jalaludinii showed comparable performance to that of commercial phytase. However, the anaerobic nature of this bacterium renders difficulty in the use of live cells as feed supplement in commercial poultry production. Therefore, this study was conducted to determine a suitable method to preserve phytase activity of M. jalaludinii regardless of cells viability. Mitsuokella jalaludinii was grown in MF medium under anaerobic condition and the cells were subjected to various treatments to preserve the enzyme, including bead beating, compressed air, moist heat, dry heat and freeze-drying under aerobic condition. The results showed that the total number of viable cells were significantly (p
Keywords: Anaerobic bacteria; enzyme; freeze dry; phytase activity; preservation